1971
DOI: 10.1111/j.1365-246x.1971.tb02187.x
|View full text |Cite
|
Sign up to set email alerts
|

The Spectral Determination of Depths to Buried Magnetic Basement Rocks

Abstract: The power spectrum of airborne magnetometer total intensity field profiles can be used to determine average depth values to buried magnetic rocks. These depths are established from the slope of the log-power spectrum at the lower end of the total wavenumber, or spatial frequency band. The method is based on the assumption that the magnetic effect of the basement surface can be simulated by an uncorrelated distribution of magnetic line sources, and is independent of the magnetic declination and inclination for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

1978
1978
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(32 citation statements)
references
References 12 publications
0
31
0
1
Order By: Relevance
“…This method provides a relationship between the spectrum of the anomalies and the depth of sources in the frequency domain. TREITEL et al (1971) have used this method to map geologic structures from gravity data observed at the surface. DIMITRIADIS et al (1987) have generalized this approach to gravity data.…”
Section: Methodsmentioning
confidence: 99%
“…This method provides a relationship between the spectrum of the anomalies and the depth of sources in the frequency domain. TREITEL et al (1971) have used this method to map geologic structures from gravity data observed at the surface. DIMITRIADIS et al (1987) have generalized this approach to gravity data.…”
Section: Methodsmentioning
confidence: 99%
“…The Spector and Grant method uses the gridded data for computing the 2-D power spectrum, then annular averages to find the depths of anomalous sources due to the uncorrelated distribution of the ensemble of prismatic bodies. The spectral analysis method found various applications in the interpretation of gravity and magnetic data (SPECTOR and GRANT, 1970;TREITEL et al, 1971, NEGI et al, 1986. The depth value can be calculated from the slope of the straight line fitted to the plot of the log power spectrum versus the wavenumber.…”
Section: Scaling Spectral Methodsmentioning
confidence: 99%
“…It has become a widely used tool for interpretation of potential field data, especially for depth estimation. This approach has been developed by many workers (e.g., [20][21][22]). However, it was proved that the International Journal of Geophysics FFT introduces unacceptable distortions at high frequencies, which describe the response of shallow sources.…”
Section: Spectral Analysis Of the Ground Magnetic Survey Datamentioning
confidence: 99%